Abondance et spectre de taille des macroinvertébrés benthiques lotiques en relation avec l'abondance du périphyton. - Nadon, Daniel. (University of Ottawa (Canada), 1993)
Twelve streams of the Ottawa-Hull area were sampled between May 9, 1990 and August 1, 1991 to examine how benthic macroinvertebrate biomass and size spectra varied in relation to periphyton biomass. Among sites, non-filter-feeding macroinvertebrate biomass is correlated positively to periphyton biomass. This relation is defined by the regression equation: Log(BNF) = 1.64 + 0.41*Log(peri) (r$\sp2$ = 0.50, F = 9.9, p = 0.01, S$\sp2$ = 0.15, n = 12). The logarithm of the mean annual periphyton biomass explains 50% of the variance encountered in the logarithm of the mean annual non-filter-feeding macroinvertebrate biomass. This figure goes up to 70% if only samples collected between mid-July and mid-August are considered. The normalized size spectra of all benthic macroinvertebrates from city streams is shifted to the right along the abcissa compared to the normalized size spectra of other streams. This shift indicates a greater individual average weight for macroinvertebrates in city streams compared to macroinvertebrates from Gatineau Park. This shift is not solely related to the eutrophic level of the stream. Other studies in controlled environments will be needed to determine the cause of this shift.
Keywords: Biology, Ecology.